Sugar signals pedal the cell cycle! - Rawat, Sanjay Singh; Laxmi, Ashverya (Frontiers in Plant Science, 2024)
Cell cycle involves the sequential and reiterative progression of important events leading to cell division. Progression through a specific phase of the cell cycle is under the control of various factors. Since the cell cycle in multicellular eukaryotes responds to multiple extracellular mitogenic cues, its study in higher forms of life becomes all the more important. One such factor regulating cell cycle progression in plants is sugar signalling. Because the growth of organs depends on both cell growth and proliferation, sugars sensing and signalling are key control points linking sugar perception to regulation of downstream factors which facilitate these key developmental transitions. However, the basis of cell cycle control via sugars is intricate and demands exploration. This review deals with the information on sugar and TOR-SnRK1 signalling and how they manoeuvre various events of the cell cycle to ensure proper growth and development.In the budding yeast, two TOR genes are present which encode for the paralogs, Tor1 and Tor2, that make up the catalytic subunits of the TORC1 and TORC2 complexes, respectively, though TORC1 can also accommodate Tor2 at its active site (Loewith et al., 2002;Wedaman et al., 2003). Moreover, the structural aspects and composition of TORC1 and TORC2 are distinct, leading to rapamycin insensitivity in the latter (Loewith and Hall, 2011). On the other hand, in animals, only TOR, encoded by a single gene makes up the catalytic subunit of both mTORC1 and mTORC2 (Saxton and Sabatini, 2017). The two multimeric complexes vary in their overall subunit composition and therefore have specialized functions (Emmerstorfer-Augustin and Thorner, 2023). As in yeast, the mTORC1 in mammals and TORC1 in plants (hereafter TOR, since it lacks the TORC2 complex), control various aspects of cell cycle, growth and autophagy, while the TORC2/mTORC2 complexes regulate actin cytoskeleton dynamics